Condition of religious care provided to hospitalized patients - abdolhosein emamisigaroudi; Hadi Basiri; jila Shekani; Ali Nouri Saeed; Leila Rouhi Balasi; Ehsan Kazemnejad Leili (Guilan University of Medical Sciences, 2015)
Introduction: Faith and religious beliefs are important and even the most fundamental assets of life. Physical and spiritual health and also length of life is owed to beliefs of people. A Muslim considers performing religious affairs as the most and best way of religious commitment. Providing religious care to those in needs is patient's right and it's an important religious duty. Objective: This study aimed to determine the condition of religious care provided to hospitalized patients in selected educational centers in Rasht city. Methods: This is a descriptive-analytic study. One hundred patients hospitalized in medical-surgical units in one of the selected hospitals in Rasht city in 2011were chosen by convenience sampling method. Data were collected through a researcher made questionnaire to survey the religious care provided to hospitalized patients that included 20 questions in domains of sex conformity, condition of patient privacy, praying condition, visiting and confidentiality and condition of praying facilities in hospital. Collected data were analyzed by using descriptive statistics and Friedman test. Results Most samples (72%) were older than 45 years. Most were female (55.6%) and housewife (55.4%). 85% had education under diploma. Patients had the most sex conformity with nurses and least conformity with the doctors but it was statistically non-significant (p<0.097). Patient privacy compliance and condition of praying was unfavorable and there was no significant difference between different units (p=0.009). Conclusion: Overall findings indicated that care provided was unsatisfactory in most domains surveyed. Study results require authorities to increase the knowledge of personnel and promote the hospital structure.